2014
DOI: 10.1177/193758671400800111
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Design of the Built Environment on People with Dementia: An Evidence-Based Review

Abstract: Results of this review indicate that, with the exception of cognition, specific design interventions are beneficial to the outcomes of people with dementia. Overall, the field of environmental design for people with dementia is well researched in many aspects and only few gaps in knowledge were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
171
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(179 citation statements)
references
References 153 publications
(260 reference statements)
1
171
0
7
Order By: Relevance
“…Marquardt previously reviewed studies of the impact of sensory enhancement and concluded that there is sufficient evidence to recommend the positive effect of appropriate stimulus but with a proviso of a need to identify appropriate levels (Marquardt et al, 2014). Campo highlighted the importance of points of interest within the environment to social interactions; however, also highlighted the importance of finding a balance and the dangers of over stimulation and distraction (Campo & Chaudhury, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Marquardt previously reviewed studies of the impact of sensory enhancement and concluded that there is sufficient evidence to recommend the positive effect of appropriate stimulus but with a proviso of a need to identify appropriate levels (Marquardt et al, 2014). Campo highlighted the importance of points of interest within the environment to social interactions; however, also highlighted the importance of finding a balance and the dangers of over stimulation and distraction (Campo & Chaudhury, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This study contributes a breadth of insight into immediate observable effects of built environment qualities on everyday activities. Capturing short snippets of interactions meant that longer term effects such as the impact of exposure to bright light on mood noted in previous studies (Joseph et al, 2015;Marquardt et al, 2014) were therefore not captured by this work. Therefore, the findings would be extended by consideration alongside results of other methods including for example longitudinal sensor-based collection of activity levels and environmental measures.…”
Section: Contributions and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural design choices in residential aged care have been found to directly influence resident outcomes [13]. Improvements in areas such as behaviour, function, well-being, and care outcomes have been linked to specialised environmental design interventions [14]. In contrast, higher rates of depressive symptoms have been linked to larger facilities as well as facilities located in non-urban areas [15].…”
Section: Introductionmentioning
confidence: 99%
“…D. Moore, VanHaitsma, Curyto, & Saperstein, 2003;Nahemow & Lawton, 1973). In this way modification of the home to meet changing needs has been shown to be effective in enabling people to remain at home through increasing age and long term illness (Alzheimer's Society, 2014;Marquardt, Bueter, & Motzek, 2014). Evidence shows the risk of falls and some cognitive symptoms (such as impaired memory, agitation and aggression) can be ameliorated through changes within the physical environment (e.g.…”
Section: Introductionmentioning
confidence: 99%